(untitled) (Repertorio Científico, 2024)
The list of vertebrate species registered during twelve visits in the morning, between August and September 2022, and April and May 2023, at the Los Llanos Experimental Station, in La Garita of Alajuela, is presented. 69 species of vertebrates were recorded, of which one was a mammal, another a reptile and the other birds. Eight species were observed during most census days (11 to 12 days), while 36 species were only recorded once or twice. Twelve recorded species have a conservation status. The variety of habitats present in the station and its climatic conditions influence the species recorded. It is suggested to establish a monitoring program that completes the registration of vertebrate species and provides information to take management measures to meet the objective of the station.